The Effect of Entrepreneurial Education on Business Performance Through Business Collaboration as a Variable of Meditating International Business Management Students of Ciputra University Surabaya - Rossella Lianna Himawan; Junko Alessandro Effendy (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Reiterating on a research done by the Ministry of Industry, in 2023, Indonesia has maintained an entrepreneurship proportion of just 3.47% inclusive of the entire population, and this is grossly low compared to the 10-14% mark set by developed nations. There are a multitude of reasons which contribute to low amounts of entrepreneurial education, some basic ones are skilled human resources deficiency, lack of the curriculum, etc. Hypothetically, if a correlation exists between excellent entrepreneurs and entrepreneurial education, then the relevance and role of business partnership cannot be overlooked, especially considering the challenges faced for which business partnership acts as a solution. This research was conducted using a quantitative approach in conjunction with purposive sampling as a non probability sampling strategy. An online survey was created to gather data on 181 participants considering the data collection method. In SmartPLS 4.0, Structural Equation Modeling (SEM) is used as a data analysis method in this study. The results indicate that entrepreneurial education has a positive and significant effect on business collaboration and business performance, while business collaboration has a positive and significant impact on business performance. This study indicates that business collaboration mediates the relation between entrepreneurial education and business performance.